PEMBERDAYAAN MASYARAKAT DESA MELALUI PENDAMPINGAN HUKUM UNTUK MENINGKATKAN KESADARAN DAN PERTISIPASI DALAM MENGELOLA KEUANGAN DESA DI DESA JAGARAGA LOMBOK BARAT - Sepyah Sepyah (JURDAR : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
supporting sustainable rural development. However, low legal awareness and limited community participation in village financial oversight remain significant challenges. This study aims to describe the process and impact of legal assistance as a form of community empowerment in Jagaraga Village, West Lombok, in order to improve public awareness and participation in managing village finances. This research uses a descriptive qualitative approach with data collected through interviews, observation, and documentation. The results indicate that participatory legal assistance significantly improves community understanding of village regulations and encourages their involvement in public discussions and budget monitoring forums. This program not only builds legal awareness but also fosters a stronger culture of transparency and accountability at the village level.